Say‐on‐pay judgements: the two‐strikes rule and the pay‐performance link. (13th July 2018) - Liang, Yimeng; Moroney, Robyn; Rankin, Michaela
Abstract: We undertake an experiment to explore shareholder voting behaviour when the pay‐performance link is weak or strong; and when there has (has not) been a first strike in the preceding year. We find shareholders are more supportive of a remuneration package evidencing a strong pay‐performance link than a weak link. Further, shareholders are less supportive of a remuneration package when there has been a first strike in the preceding year than when there has not been a first strike. Importantly, we find that a first strike reduces the effect of the pay‐performance link on voting intentions.